2018
DOI: 10.1007/s00380-018-1145-1
|View full text |Cite
|
Sign up to set email alerts
|

Serial assessment of endothelial function 1, 6, and 12 months after ST-elevation myocardial infarction

Abstract: Knowledge about the changes in endothelial function after ST-elevation myocardial infarction (STEMI) is of substantial interest, but serial data are scarce. The aim of the present study was to noninvasively evaluate whether endothelial function, as assessed shortly after primary percutaneous coronary intervention (PPCI) for STEMI, may improve until 12-month follow-up. This prospective observational cohort study was performed in patients in the RESPONSE randomized trial who participated in a substudy and underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…shear stress, which in turn ameliorates the endothelialdependent vasodilatation. 14 Kandhai-Ragunath et al 15 assessed endothelial function using RH-PAT four to six weeks after primary percutaneous coronary intervention and demonstrated that a better endothelial function is anticipated in patients with acute myocardial infarction and patent culprit coronary arteries diagnosed during the intervention. Heinen et al 16 reported local changes in endothelial function within atherosclerotic occlusions that occurred after balloon angioplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…shear stress, which in turn ameliorates the endothelialdependent vasodilatation. 14 Kandhai-Ragunath et al 15 assessed endothelial function using RH-PAT four to six weeks after primary percutaneous coronary intervention and demonstrated that a better endothelial function is anticipated in patients with acute myocardial infarction and patent culprit coronary arteries diagnosed during the intervention. Heinen et al 16 reported local changes in endothelial function within atherosclerotic occlusions that occurred after balloon angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Kandhai-Ragunath et al. 15 assessed endothelial function using RH–PAT four to six weeks after primary percutaneous coronary intervention and demonstrated that a better endothelial function is anticipated in patients with acute myocardial infarction and patent culprit coronary arteries diagnosed during the intervention. Heinen et al.…”
Section: Discussionmentioning
confidence: 99%